Hard metal lung disease: a case series - Mizutani,Rafael Futoshi (2016)
ABSTRACT Objective: To describe diagnostic and treatment aspects of hard metal lung disease (HMLD) and to review the current literature on the topic. Methods: This was a retrospective study based on the medical records of patients treated at the Occupational Respiratory Diseases Clinic of the Instituto do Coração, in the city of São Paulo, Brazil, between 2010 and 2013. Results: Of 320 patients treated during the study period, 5 (1.56%) were diagnosed with HMLD. All of those 5 patients were male (mean age, 42.0 ± 13.6 years; mean duration of exposure to hard metals, 11.4 ± 8.0 years). Occupational histories were taken, after which the patients underwent clinical evaluation, chest HRCT, pulmonary function tests, bronchoscopy, BAL, and lung biopsy. Restrictive lung disease was found in all subjects. The most common chest HRCT finding was ground glass opacities (in 80%). In 4 patients, BALF revealed multinucleated giant cells. In 3 patients, lung biopsy revealed giant cell interstitial pneumonia. One patient was diagnosed with desquamative interstitial pneumonia associated with cellular bronchiolitis, and another was diagnosed with a hypersensitivity pneumonitis pattern. All patients were withdrawn from exposure and treated with corticosteroid. Clinical improvement occurred in 2 patients, whereas the disease progressed in 3. Conclusions: Although HMLD is a rare entity, it should always be included in the differential diagnosis of respiratory dysfunction in workers with a high occupational risk of exposure to hard metal particles. A relevant history (clinical and occupational) accompanied by chest HRCT and BAL findings suggestive of the disease might be sufficient for the diagnosis.